WRITING TRANSGRESSION: PRESERVING THE LANDSCAPE OF TRADITION IN TANURE OJAIDE'S GOD'S MEDICINE-MEN & OTHER STORIES - Niyi AKINGBE (Diversitate si Identitate Culturala in Europa, 2012)
Tanure Ojaide, a celebrated Nigerian poet, is a writer who is constantly in search for an alternative social vision to the degenerating socio-political concerns in Nigeria. Social concerns mediated by orature provide the predominant framework within which his poetry collections have been analyzed. At the debut of his writing career now spanning three decades, Ojaide’s entry into the Nigerian literary landscape in 1973 was heralded by the publication of Children of Iroko. God’s medicinemen and other stories is his first attempt at writing short stories. This anthology of short stories expresses a deep moral indignation, in its denunciation of the shameful state in which the socio-cultural ethos has been compromised in contemporary Nigeria. This paper evaluates the manner in which Ojaide explores the broad theme of the break-down of social and cultural norms in Nigerian society as exemplified in God’s medicine-men and other stories. It also examines how, in the anthology, the complexity of the intersections that obtain between tradition and modernity has significantly shaped individual lives, focusing mainly on the way in which cultural hybridity serves to underscore the effect of this breakdown in contemporary Nigerian society.